Colorectal Carcinoma with Extremely Low CA19-9 - Yutaka J. Kawamura; Aika Tokumitsu; Junichi Sasaki; Shingo Tsujinaka; Takafumi Maeda; Ken Mizogami; Fumio Konishi (Gastroenterology Research and Practice)
Aim. The aim of this study is to determine the significance of postoperative sequential measurements of serum CA19-9 in patients with extremely low serum level. Patients and Methods. Serum level of CA19-9 of 1096 patients who underwent surgery was measured preoperatively and every three months after surgery for 5 years. Patients with CA19-9 level of less than 2 U/mL at the time of diagnosis were defined as Extremely Low CA19-9 (ELCA). Results. One hundred and seven patients (9.8%) were ELCA. Of these, 86 underwent surgery with curative intent. Serum levels of CA19-9 in patients who did not undergo curative resection (𝑁=12) and who developed recurrence (𝑁=10) were less than 2.0 U/mL in all occasions during followup. In all patients without recurrence, serum level of CA19-9 also remained less than 2.0 U/mL. Conclusion. In patients with extremely low CA19-9, who consist of 9.8% of colorectal carcinoma cases, postoperative sequential measurement of serum level of CA19-9 contributed neither to assessment of curability of surgical resection nor to detection of recurrence.